Polymorphous adenocarcinoma transforming to Adenoid cystic carcinoma - A case report - A.K. Anjali; Sandhya Tamgadge; Treville Pereira; Rutuja G. Vidhale; S. Sudhamani (Elsevier, 2021)
Polymorphous adenocarcinoma is an indolent salivary gland carcinoma characterized by cytologic uniformity and architectural diversity, predominantly affecting minor salivary glands, in particular the hard and soft palate. Adenoid cystic carcinoma (ACC) is an uncommon type of adenocarcinoma, a kind of malignant growth that starts in glandular tissues. It most regularly emerges in the major and minor salivary organs of the head and neck. This paper reports an instance of a 59-year-old male patient who was determined to have Polymorphous adenocarcinoma which ultimately ended up being Adenoid cystic carcinoma.